2008
DOI: 10.12741/ebrasilis.v1i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e Distribuição de Coccinelídeos (Coleoptera, Coccinellidae) Associados às Plantas Cítricas no Estado do Rio de Janeiro

Abstract: Resumo. O estudo objetivou registrar a ocorrência, fl utuação populacional das espécies de coccinelídeos e delinear a distribuição geográfi ca (Coleoptera, Coccinellidae) associados as plantas cítricas no Estado do Rio de Janeiro. Abstract. This work aimed to register the occurrence, study the population fl uctuation the ladybeetles species and to delineate the geographic distribution (Coleoptera, Coccinellidae) associated at citrus plants in Rio de Janeiro State. 11 districts situated in two regions of the Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Assim, ficou caracterizada a dominância deste artrópode no referido pomar; a espécie também foi classificada como muito abundante, muito frequente e constante porém, apresenta, normalmente, baixa ocorrência para muitos agroecossistemas (Cividanes, 2002;Guerreiro, 2005;Duarte et al, 2012;Harterreiten-Souza et al, 2012), divergindo dos resultados encontrados. A resposta observada no presente experimento pode estar intimamente relacionada com a presença de espécies de presas preferenciais por este predador (diaspidídeos) (Rodrigues et al, 2008b).…”
Section: Resultsunclassified
“…Assim, ficou caracterizada a dominância deste artrópode no referido pomar; a espécie também foi classificada como muito abundante, muito frequente e constante porém, apresenta, normalmente, baixa ocorrência para muitos agroecossistemas (Cividanes, 2002;Guerreiro, 2005;Duarte et al, 2012;Harterreiten-Souza et al, 2012), divergindo dos resultados encontrados. A resposta observada no presente experimento pode estar intimamente relacionada com a presença de espécies de presas preferenciais por este predador (diaspidídeos) (Rodrigues et al, 2008b).…”
Section: Resultsunclassified
“…The different insect population densities throughout the year are directly related to the climatic conditions, the characteristics of the studied region, and possibly due to the presence of natural enemies that can act in naturally controlling this species. Coccinellids, such as Pentilia egena Mulsant, Coccidophilus citricola Brèthes, Azya luteipes Mulsant, Cycloneda sanguinea L. and Scymnus spp., are important natural enemies of S. articulatus in citrus (Rodrigues et al, 2008).…”
Section: -6mentioning
confidence: 99%
“…Studies dealing with the occurrence of arthropod predators in citrus orchards are rare in Brazil. The information available is related to coccinellids, lacewings, and syrphids (Rodrigues et al 2004), ants (Carvalho et al 2000), wasps (Galvan et al 2002), and mites (Silva & Oliveira 2006). Some studies have reported on the occurrence of parasitoids in orchards (Garcia et al 2001;Jahnke et al 2005).…”
Section: Introductionmentioning
confidence: 99%